Esports buffs: the perceived role of fans and fandoms in U.S. collegiate programs - Cote, Amanda C.; Rahman, Md Waseq Ur; Foxman, Maxwell; Wilson, Andrew; Harris, Brandon C.; Can, Onder; Hansen, Jared C. (Frontiers in Sports and Active Living, 2024)
Collegiate esports-organized competitive gaming-has expanded rapidly in the United States, drawing in student players, broadcasters, and support staff, as well as university employees. Universities have invested financially in esports, hoping to capitalize on gaming fandom to attract prospective students and enhance campus community integration. Little research, however, addresses collegiate esports fandom in depth. Drawing on thirty-one in-depth interviews with collegiate esports players, student workers, program directors, and administrators, this article investigates how collegiate esports participants perceive and discuss their fans. We identify three central themes related to fans in the dataset: discussions of fans' role in the collegiate esports environment, comparisons between esports and traditional sports fans, and concerns about the underutilization of fans within collegiate esports spaces. Subsequently, we theorize these themes through existing research on professional esports and traditional collegiate sports fandoms, as well as through the concept of "fan labor," or how the productive work of fans provides value to the nascent industry. This article thus not only specifically explores how collegiate esports programs are normalizing fan labor as an essential part of their practices, but also questions who benefits from this relationship and how. Investigating collegiate esports fans as an under-researched group additionally provides a new perspective on how fan labor integrates with media industries more broadly.